Evaluation of a freely available sensor racket as a diagnostic and training tool in elite badminton - Gawin, W.; Herbstreit, A.; Fries, U.; Maiwald, C. (International Journal of Racket Sports Science, 2022)
To avoid the drawbacks of optical video-based motion capture systems and due to the ongoing miniaturization of integrated sensors, an increasing variety of sensor-based systems has been used for motion capture in sports. Meanwhile, there are ready-made, commercially available solutions that claim to be capable of recording reliable kinematic data. This research project focuses on the question of whether a commercially available badminton racket with an integrated sensor device (Oliver® Plasma TX 5) provides meaningful data for diagnostic and training purposes in elite sports. Therefore, 16 elite badminton players executed jump smashes using this sensor racket while the kinematics of the stroke technique were recorded using a high speed video-based system. Bland-Altman plots were applied to analyze the agreement between the two systems. The plots revealed a systematic bias and 95% limits of agreement ranging from 6% to 23%: The detection of stroke techniques showed a 42% rate of success. These data show that the measurement accuracy of the sensor racket is not sufficient for use in diagnostics or training. Future development of the sensor racket could include a method to calibrate the system prior to a measurement, in addition to correcting the underlying algorithm to reduce the bias.